Kritik Sosial dalam Cerpen Ina Tonu Karya Silvester Petara Hurint (International Forum of Researchers and Lecturers, 2025)
This study aims to reveal and describe social criticism in the short story Ina Tonu by Silvester Petara Hurint. This study uses a sociology of literature approach and a descriptive qualitative method. The results of the study indicate that the short story Ina Tonu by Silvester Petara Hurint displays strong social criticism of various aspects of community life. The social criticism in this short story can be concluded as follows, (1) social criticism of the elimination of local culture, (2) social criticism of the loosening of kinship relations in society, (3) social criticism of forced migration of women and the fading of cultural heritage, (4) social criticism of the commercialization of culture and the fading of the sacred meaning of weaving, (5) social criticism of the stigma against indigenous women who are traumatized and sick, and (6) social criticism of the tendency of modern society to interpret tradition in a limited way.